(untitled) ("Journal "U". Economy. Management. Finance.", 2019)
The article presents the study on the role of marketing research in the business activity of a company. Main research methods, such as observation, focus groups, survey, the Rockeach value scaling, ethnographic and expert assessments are also described in detail.